Exogenous Putrescine Alleviates Drought Stress by Altering Reactive Oxygen Species Scavenging and Biosynthesis of Polyamines in the Seedlings of Cabernet Sauvignon - Zhao, Jiaqi; Wang, Xuefei; Pan, Xingbo; Jiang, Qianqian; Xi, Zhumei (Frontiers in Plant Science, 2021)
Climate change imposes intensively dry conditions in most grape-rowing regions. Drought stress is one of the most devastating abiotic factors threatening grape growth, yield, and fruit quality. In this study, the alleviation effect of exogenous putrescine (Put) was evaluated using the seedlings of Cabernet Sauvignon (Vitis vinifera L.) subjected to drought stress. The phenotype, photosynthesis index, membrane injury index, and antioxidant system, as well as dynamic changes of endogenous polyamines (PAs) of grape seedlings, were monitored. Results showed that drought stress increased the membrane injury index (MII), lipid peroxidation, and the contents of reactive oxygen species (ROS) (H2O2 and O2.−), while it decreased antioxidant enzyme activity and the net photosynthesis rate. However, application of Put alleviated the effects of drought stress by altering ROS scavenging, enhancing the antioxidant system, and increasing the net photosynthesis rate. Put distinctly increased the activity of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), as well as the contents of ascorbic acid (AsA) and glutathione (GSH). Meanwhile, exogenous Put also promoted the metabolism of endogenous PAs by upregulating their synthetic genes. Our results confirmed that the exogenous application of Put can enhance antioxidant capacity as well as alter the PA pool, which provides better drought tolerance for Cabernet Sauvignon seedlings.